Lao People's Democratic Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper examines the main causes for the surge in dollarization in the Lao People's Democratic Republic (Lao PDR). It explores various strategies that may be adopted to maintain low inflation and thus, indirectly, encourage the use of the national currency. The paper highlights that foreign currencies now account for the largest component of the domestic money supply. This situation, although encouraging in a country with poorly developed financial institutions, poses several challenges for the authorities.